Role of fluorodeoxyglucose-positron emission tomography in predicting the pathological response and prognosis after neoadjuvant chemoradiotherapy for locally advanced non-small-cell lung cancer. (11th May 2022) - Tanahashi, Masayuki; Suzuki, Eriko; Yoshii, Naoko; Watanabe, Takuya; Tsuchida, Hiroyuki; Yobita, Shogo; Iguchi, Kensuke; Uchiyama, Suiha; Nakamura, Minori
Abstract: OBJECTIVES: The present study compared the utility of fluorodeoxyglucose-positron emission tomography (FDG-PET) and computed tomography (CT) for predicting the pathological response and prognosis following neoadjuvant therapy for locally advanced non-small-cell lung cancer (NSCLC). METHODS: This retrospective analysis included 72 patients in whom adjacent structures showed involvement and/or cN2 NSCLC who received induction chemoradiotherapy (ICRT) and subsequent surgery at our hospital from 2008 to 2019. FDG-PET and CT were performed in all patients before and after ICRT using the same scanner with similar techniques. We calculated the reduction in the maximum standardized uptake value in FDG-PET (ΔSUVmax) and tumour size on CT (ΔCT-size) before and after ICRT and investigated the relationship between the pathological response and prognosis. RESULTS: The disease response was classified as a major pathological response in 43 patients, and a minor response in 29 patients. ΔSUVmax 60% and ΔCT-size 30% were identified as the optimal cut-off values for predicting a major pathological response. ΔSUVmax was superior to ΔCT-size in terms of sensitivity, specificity, positive predictive value and negative predictive value. Furthermore, ΔSUVmax was superior to ΔCT-size for predicting the prognosis. CONCLUSIONS: Based on the results of the present study, FDG-PET appeared to have greater utility than CT in predicting the pathological response following ICRT and the postoperative prognosis in patients with locally advanced NSCLC. Abstract : Worldwide, non-small-cell lung cancer (NSCLC) is one of the most frequent causes of cancer-related mortality [1].